(untitled) (Medical Forum Monthly, 2024)
Objective: Scheme of this study was to observe the contingency of thrombocytopenia in patients with malaria. Study Design: Prospective Study Place and Duration of Study: This study was conducted at the Department of Medicine, Saidu Teaching Hospital, Swat from Jan 2015 to Nov 2016. Materials and Methods: In the Medical unit of Saidu Teaching Hospital, this study was performed on 100 patients having malaria who were positive for malaria parasite.Platelet count was done at the time of presentation by hematology analyzer. Results: 16 patients were found to have normal platelet count. 68 patients were having platelet count between 50000-150000(mild thrombocytopenia). 11 patients were having platelet count between 20000-50000(moderate thrombocytopenia). 5 patients were having platelet count less than 20000 (severe thrombocytopenia). Male female ratio in this study was almost equal 1.04:1 i.e. 51 males and 49 females. Thrombocytopenia was more common in age group 31-50 years. Conclusion: Mild to moderate thrombocytopenia is found in malaria. Thrombocytopenia is not diagnostic of malaria but can raise malaria suspicion.